PERSONAL BRANDING PT. VALE INDONESIA DI INSTAGRAM - Islaq Hastita Hamzah; Tuti Bahfiarti; M. Iqbal Sultan (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
Personal branding by a company is important to build a positive image for itsaudiences. One of the social media that is widely used is Instagram because it can bringup two-way communication and audio-visual sharing. PT. Vale Indonesia Tbk., a nickelmining company chose Instagram to build its personal branding as a way of marketingitself and to be remembered by the audience as a mining company that has excellencewith professional goals.This research is qualitative research using non-participant observation data collectiontechniques and documentation by looking at the content uploaded, content in the formof images and captions.The results of the study show that PT. Vale Indonesia builds personal branding as amining company that cares for fellow human beings and sustainable nature, supportslocal MSMEs, and upholds gender equality.